Affimer Proteins: Theranostics of the Future?. Issue 4 (April 2018) - Kyle, Stuart
Abstract : Affimer proteins can bind to a wide variety of target molecules. They can complement and represent a promising alternative to conventional antibodies as they can target molecules with high affinity, specificity, and stability. In addition, they can be selected and expressed in bacterial and mammalian systems. Affimer protein technology shows promise as a tool in the biologist's arsenal of the future in imaging, diagnostic, and therapeutic applications.